1999
DOI: 10.1093/carcin/20.7.1369
|View full text |Cite
|
Sign up to set email alerts
|

Gap junctional intercellular communication and connexin43 expression in human ovarian surface epithelial cells and ovarian carcinomas in vivo and in vitro

Abstract: Gap junctional intercellular communication (GJIC) and the expression of gap junction proteins (connexins) are frequently decreased in neoplastic cells and have been increased by cAMP and retinoids. GJIC and connexin expression were investigated in early passage normal human ovarian surface epithelial (HOSE) cells, human ovarian adenocarcinoma cell lines (CaOV-3, NIH:OVCAR-3, SK-OV-3 and SW626) and surgical specimens of human serous cystadenocarcinomas. We hypothesized that GJIC and connexin expression would be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(27 citation statements)
references
References 28 publications
1
26
0
Order By: Relevance
“…In larger lung tumors, Cx32 and Cx40 are down-regulated, but Cx37, Cx43, and Cx45 are expressed (Isakson et al, 2001a(Isakson et al, ,b, 2003Udaka et al, 2006). In other cases, such as ovarian adenocarcinomas and cervical cancer, GJIC is dramatically reduced (Hanna et al, 1999;Umhauer et al, 2000;Aasen et al, 2005;Gershon et al, 2008). In this situation, because GJIC is already essentially absent, the effect of platinating reagents described in the present study would not occur, but in the former cases, the effect on the efficacy of the drugs due to effects on GJIC could occur.…”
Section: Downloaded Frommentioning
confidence: 55%
“…In larger lung tumors, Cx32 and Cx40 are down-regulated, but Cx37, Cx43, and Cx45 are expressed (Isakson et al, 2001a(Isakson et al, ,b, 2003Udaka et al, 2006). In other cases, such as ovarian adenocarcinomas and cervical cancer, GJIC is dramatically reduced (Hanna et al, 1999;Umhauer et al, 2000;Aasen et al, 2005;Gershon et al, 2008). In this situation, because GJIC is already essentially absent, the effect of platinating reagents described in the present study would not occur, but in the former cases, the effect on the efficacy of the drugs due to effects on GJIC could occur.…”
Section: Downloaded Frommentioning
confidence: 55%
“…The particular composition of CONNEXIN subunits within a gap junction determines the type of molecule that can be transported 16 . Much remains to be learned about how the specific combination of connexins facilitates tissue interactions, but it is clear, again, that generalizations should be avoided, as the expression patterns (and probably the function) of connexins are tissue dependent and change during tumour progression 17,18 . For example, some breast cancer cells upregulate connexin 32 (Cx32) 19 , but loss of Cx32 contributes to hepatocellular carcinoma 20,21 ; Cx43 inhibits tumorigenicity of lung, cervical and bladder carcinoma cells [22][23][24] , but has no effect on squamous cell carcinomas 25 ; and other connexins can facilitate cell adhesion during metastasis 26 .…”
Section: Box 1 Epithelial Cell Polarity and Tumorigenesis In Drosophilamentioning
confidence: 99%
“…With regard to transformation, a number of immunohistochemical and molecular studies have generally suggested an overall decrease in Cx43; this was the case in high-grade prostate carcinoma [10], in ovarian carcinomas in vivo and in vitro [11], in cervical dysplasia and the HeLa cell line [12], and in cutaneous basal and squamous cell carcinomas [13]. Data on Cxs in breast tumors are scanty; various reports pointed to a decreased Cx43 expression in some human and murine breast carcinomas and cell lines [14] and heterogeneous Cx43 reactivity in approximately 50% of breast carcinomas with staining of some stromal cells [15].…”
Section: Introductionmentioning
confidence: 99%